Burden of chronic illness and associated disabilities in Bangladesh: Evidence from the Household Income and Expenditure Survey - Marufa Sultana (KeAi Communications Co., Ltd., 2017)
Objective: The purpose of this study was to investigate the distribution of chronic illness and associated disability, out-of-pocket payment (OOPP), and other related factors using survey data from Bangladesh. Methods: This study analyzed Bangladesh Household Income and Expenditure Survey data that include socio-economic and demographic data, such as consumption, expenditures, and assets, along with information regarding chronic illness and disability. Multiple linear regression models were used to identify factors significantly associated with OOPP. Furthermore, a binary Logistic regression model was employed to assess the association of the explanatory variables with disability status. Results: A higher prevalence of chronic illness was found for those with chronic gastritis (18.70%), and 41.92% of the population had at least one side disability. The average OOPP healthcare expenditure for chronic illness was estimated to be US$7.59. Higher OOPP was found among the upper 2 wealth quintiles. Overall OOPP health expenditure was significantly higher among individuals with an associated disability (PÂ <Â 0.001). The likelihood of having an associated disability was higher among those individuals with a lower education level (ORÂ =Â 2.36, 95% CI: 1.95â4.06), those who not earning an income (ORÂ =Â 2.85, 95% CI: 2.53â3.21), those who did not seek care (ORÂ =Â 1.73, 95% CI: 1.57â1.90), those who sought care from a pharmacy (ORÂ =Â 8.91, 95% CI: 7.38â10.74), and those in the lowest wealth quintile (ORÂ =Â 7.21, 95% CI: 6.41â8.12). Conclusions: The high OOPP illustrates the necessity of financial risk protection for the population at low socio-economic status. Therefore, we recommend that the government strengthen the healthcare system with appropriate support directed to the rural and elderly populations. Keywords: Chronic illness, Disability, Out-of-pocket payments, Burden, Bangladesh